Component Design and Strength Analysis of Coffin Lowering Machine for COVID-19 Corpse: A Problem-Based Learning - Khoiriyah, Nisa; Alfatih, Shahreza Agung; Munir, Misbakhul; Triawan, Farid (Indonesian Journal of Multidiciplinary Research, 2021)
The increasing number of deaths due to COVID-19 followed by an excessive number of burials had risen the emergence of a safety plan, supporting the burial process to minimize the dangerous impact on the human. The conventional way of burying the corpse with infectious disease in Indonesia utilizes ropes to lower the coffin and involves four to eight people. However, this is not practical because it is energy-wasting and crowding. This paper aims to propose a design of a safe, practical, and robust coffin lowering machine. The proposed design is available for all ages with a weight of up to 200 kg. The design has a 2000 x 600 x 750 mm dimension, in which the width can be extended from 600 to 1000 mm. The straps for lowering the coffin are mounted on the left and right-side shafts. Each of the components is connected with a pin joint. Then, the components are analyzed by calculating the static and fatigue strength to obtain the safety factor and to determine the service life. As a result, the proposed design demonstrates the safety factors for static and fatigue condition that are higher than one, indicating it can be considered for fabrication. In addition, the presented work can be referred as a problem-based learning case study in Machine Element Course.